2020
DOI: 10.1103/physrevresearch.2.033491
|View full text |Cite
|
Sign up to set email alerts
|

Quantum damping of skyrmion crystal eigenmodes due to spontaneous quasiparticle decay

Abstract: Skyrmion crystals support chiral magnonic edge states akin to electronic quantum Hall edge states. However, magnonic topology relies on the harmonic approximation, neglecting ubiquitous magnon-magnon interactions that yield a finite zero-temperature quantum damping. We demonstrate that spontaneous quasiparticle decay in two-dimensional ferromagnetic skyrmion crystals is a delicate issue, with the quantum damping ranging over several orders of magnitude. Flat magnon bands cause exceptionally strong spontaneous … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 153 publications
0
13
0
Order By: Relevance
“…1(a)] where, unlike previous proposals, there is no need to tune the laser frequency to be at resonance with internal skyrmion magnon modes [24,25]. The magnon bands supported by a static skyrmion crystal can also be topological in reciprocal space [26][27][28][29][30][31]. We show that a topological phase transition in the Floquet magnon spectrum can be driven by a terahertz laser [see Fig.…”
Section: Introductionmentioning
confidence: 81%
“…1(a)] where, unlike previous proposals, there is no need to tune the laser frequency to be at resonance with internal skyrmion magnon modes [24,25]. The magnon bands supported by a static skyrmion crystal can also be topological in reciprocal space [26][27][28][29][30][31]. We show that a topological phase transition in the Floquet magnon spectrum can be driven by a terahertz laser [see Fig.…”
Section: Introductionmentioning
confidence: 81%
“…prepared 88,159,160 . More interestingly, topological magnons, chiral magnonic edge state, as well as hybrid and quantum magnonic phenomena were predicted in SMCs in recent works [92][93][94][95][96][97][98]103,106 . According to the spatial dimension of the periodical skyrmion arrangement, SMCs can be classified into two types: 1D-SMCs [88][89][90][91] and 2D-SMCs 92-99 .…”
Section: What Are Skyrmion Based Magnonic Crystals?mentioning
confidence: 99%
“…However, the study of quantum magnonic phenomena in SMCs is still lacking. In 2020, A. Mook et al reported a new theoretical study on a quantum-mechanical many-body phenomenon of propagating magnons in SMCs which is called spontaneous quasiparticle decay (SQD) 106 . SQD of magnons is a nonlinear magnon scattering process during which a propagating magnon is scattered into two other magnons while the initial magnon mode is close to the flat magnon bands corresponding to the anticlockwise, breathing, or clockwise mode of the skyrmion lattice.…”
Section: -2 Hybrid and Quantum Phenomena Of Magnonsmentioning
confidence: 99%
See 2 more Smart Citations